CORRELATION OF EMOTIONAL EATING AND NUTRITIONAL STATUS AMONG ADOLESCENTS IN SURABAYA - Rahmawati, Anisah Firdaus; Arini, Shintia Yunita; Atmaka, S.Gz, MPH, Dominikus Raditya; Kusuma, Ardyanisa Raihan; Putri, Sheila Amara; Vidianinggar, Mutiara Arsya Wijanarko; Nor, Norfezah Md; Shahid, Nadiatul Syima Mohd (Universitas Airlangga, 2025)
Adolescence is an important period of growth because the growth spurt which occurs is the peak of physical and emotional growth and development. Adolescents often experience stress in learning at school so they need good stress coping mechanisms. One coping mechanism that is often used is to apply emotional eatingThis study aims to examine the correlation between emotional eating and the nutritional status of students at SMAN 5 Surabaya. A cross-sectional method was applied involving 91 students. Nutritional status was assessed using BMI-for-age Z-scores according to WHO Anthro Plus standards, while emotional eating was evaluated through the Eating Evaluation due to Emotions and Stress (EADES) questionnaire. The findings showed that 35.2% of students were classified as overweight, and 16.5% as obese. Additionally, 71.4% of the participants reported experiencing emotional eating. A significant association was found between emotional eating and excessive nutritional status (p=0.010). It can be concluded that emotional eating directs teenage students to a nutritional status that tends to be higher; this will have an impact on the growth and development adolescents physically and emotionally. Students are expected to have better stress coping so they don't experience emotional eating.